Some properties of primitive matrices over Bezout B-domain - Shchedryk, V.P. (Algebra and Discrete Mathematics, 2005)
The properties of primitive matrices (matrices
for which the greatest common divisor of the minors of maximal
order is equal to 1) over Bezout B - domain, i.e. commutative
domain finitely generated principal ideal in which for all a,b,c with
(a,b,c) = 1,c 6= 0, there exists element r ∈ R, such that (a+rb,c) =
1 is investigated. The results obtained enable to describe invariants
transforming matrices, i.e. matrices which reduce the given matrix
to its canonical diagonal form.